Virtual communities model using ontology of group classification for research communities. - Eri, Zeti Darleena; Abdullah, Rusli; A. Jabar, Marzanah; Azmi Murad, Masrah Azrifah (2012)
Virtual communities are becoming importance in many organizations, particularly in the institute of higher learning (IHL). Research communities are common practice in many IHLs, which are form based on similar research interest or research area. With proper internet infrastructure, the research communities formed virtual communities. However, the virtual communities of research communities are lacking in proper management in managing groups and managing groups' knowledge. Ontology is known to support standardization of the terms used to represent knowledge in a particular domain and ontology design is useful to model virtual communities. Finding the right people to collaborate is the main Knowledge Management (KM) perspective that we adopted in our study. But, the current situation of research communities has not met the KM perspective that we adopted due to the limitation of channel in finding the right people to work together. The objectives of the paper are: 1) to classify virtual communities in research communities of IHL and 2) to model virtual communities based on similar research interest using ontology. In order to achieve the objective, we are using ontology to classify and to model virtual communities based on related work. Finally, the outcome of the paper can be used to model virtual communities of another IHL.